Hemodynamic durability of transcatheter aortic valves using the updated Valve Academic Research Consortium‐2 criteria. Issue 4 (12th October 2018) - Kumar, Arnav; Sato, Kimi; Banerjee, Kinjal; Narayanswami, Jyoti; Betancor, Jorge; Menon, Vivek; Mohananey, Divyanshu; Anumandla, Anil Kumar; Sawant, Abhishek C.; Krishnaswamy, Amar; Tuzcu, E. Murat; Jaber, Wael; et al.
Abstract: Objectives: We investigated the hemodynamic durability of the transcatheter aortic valves (TAVs) using the updated Valve Academic Research Consortium‐2 (VARC‐2) criteria. Background: The updated VARC‐2 consensus criteria combine flow‐dependent and flow‐independent echocardiographic parameters for hemodynamic assessment of TAVR. Data on the hemodynamic durability of TAV and clinical risk factors associated with valve hemodynamic deterioration (VHD) are lacking. Methods: All patients (n = 276) who received TAV between 2006 and 2012 and had ≥2 follow‐up echocardiograms were studied. Results: During a median follow up period of 3.3 (1.8‐4.4) years, 8 patients (3%) developed moderate to severe valve stenosis per the VARC‐2 criteria, while 20 had mild stenosis. In a Cox proportional hazards model analysis, moderate to severe stenosis by VARC‐2 criteria was associated with younger age ( P = 0.03, HR 0.94), absence of dual antiplatelet therapy (DAPT) ( P = 0.026, HR 0.18), and lower baseline left ventricular ejection fraction (LVEF) ( P = 0.006, HR 0.94). Longitudinal analysis using a mixed effect model showed that presence of stenosis by VARC‐2 criteria was associated with an increase in aortic valve mean gradient ( P < 0.001, +2.34 mmHg per year). In a subset of 93 patients with analyzable fluoroscopic images, deeper valve implantation was associated with increase in mean gradient ( P = 0.004, +0.2 mmHg per year per 1 mm increase in implantation depth). Conclusion: Despite good hemodynamic durability of TAV, patients with younger age, lower LVEF and those not on DAPT after undergoing a TAV replacement, are at a higher risk for development of VHD.